PEMBANGUNAN SISTEM YANG BERINTEGRITAS MELALUI BUDAYA INTEGRITAS DALAM UPAYA PENCEGAHAN KORUPSI DI LINGKUNGAN PEMERINTAH PROVINSI JAWA TENGAH - Kunto Nugroho Putranto (Lembaga Administrasi Negara, 2018)
Efforts to improve the provision of financing or other sources of local revenue, especially those stemming from local taxes can be done with the improved collection performance, refinement and additional types of taxes, as well as extracting resources tax revenue. Land and building tax is one part of a considerable source of revenue and the central role given dedicated space to provide its service. To provide optimal service, the District Government through the Department of Revenue Banyuwangi regency issued a payment innovation in the form of the United Nations through the drive-thru service as stipulated in the Local regulations related to land and building tax payments. With a service model that is easy and fast, making people feel comfortable and well served. And be able to increase local revenue from land and building tax sector.Keywords: corruption, integrity, corruption prevention system, and culture of integrity.